PENERAPAN METODE PEMBELAJARAN MATEMATIKA PADA GENERASI Z DI SMK N 3 BATAM - Eko Sulistiyono; Vitri Aprilla Handayani; Garry Rusmadi; Kevin (LPPM ITEBA, 2023)
Many people think that this generation in their lifetime has experienced many bad events. Therefore, the parents of the current youngest generation are very protective of them. For Generation Z, their educational journey is still quite long. This community service aims to organize community service activities for teachers at SMK N 3 Batam to apply learning methods to Generation Z. The activity of Utilizing the Mathematics Learning Model to Improve Teacher Competence at SMK N 3 Batam is carried out for one day, namely on Saturday, January 19 2022 at 09.00 – 12.30. This activity was carried out at SMK N 3 Batam. The targets in this activity are teachers/subject teachers at SMK N 3 Batam. This community service activity is carried out using lecture and practice methods. Service participants gave a good response. There are several methods that are considered effective for learning during a pandemic. What can be obtained from carrying out this activity is that it can provide information and understanding about the habits and behavior of Generation Z which can be well received and understood by the participants implementing the service activities. Besides that, it can provide information and understanding in dealing with Generation Z, which positively contributes to teachers so that it can be applied in learning